Varstvo pravnih oseb kot nosilcev človekovih pravic v Nemčiji, v Švici in v Združenih državah Amerike - Tratar, Boštjan (Pravnik, 2017)
The author reviews a book by Mirjam Baldeger, in which she presents the protection of human rights of legal entities in different countries (Menschenrechtsschutz für juristische Personen in Deutschland, der Schweiz und den Vereinigten Staaten, Begründungsmodelle der korporativen Menschenrechtsträgerschaft. Duncker & Humblot GmbH, Berlin, 2017, 841 pages). The presented work treats fully the topic of the use/effects of the constitutional rights for legal persons. The author of the book compares the constitutional systems of Germany, Switzerland, and the United States regarding the treatment of legal persons as holders of human rights. In a large part of the book, the author compares the jurisprudence of the highest courts of the compared countries (Germany, Switzerland, USA) and states those human rights which are also applicable to legal persons and those which are not. Special attention is given to situations where a legal person has a close relationship with the state, because then the legal person plays more the role of the addressee as the holder of constitutional rights. The author of the presented book deals specifically with the importance of the relationship between individuals and legal persons for the protection of human rights.
Keywords: človekove pravice; Germany; holder of the human rights; human rights; legal person; pravne osebe; recenzije; Switzerland; United States of America; varstvo pravnih oseb